Rotatable anisotropy in exchange bias bilayer and stripe domains films with uniaxial anisotropy. (1st May 2023) - Pan, Lining; Wang, Wenfeng; Gao, Yu; Zhou, Tingting; Zhuang, Xueheng; Man, Qikui
Abstract: We report the rotatable anisotropy in three magnetic film systems, including in-plane magnetized FeNi film, FeNi/FeMn bilayer and FeNi stripe domains (SDs) structure film. Omnidirectional ferromagnetic resonance driven by rotatable anisotropy can be achieved in these films. We have found that the in-plane magnetized FeNi films have a negligible rotatable anisotropy of about 1 ∼ 2 Oe. Rotatable anisotropy fields of 6.1 Oe and 5.5 Oe are found for isotropic and anisotropic FeNi/FeMn bilayers, which comes from the exchange coupling at the interface of FM and AFM layer. This magnitude is smaller than the value found in thick FeNi film where a big rotatable anisotropy field of 87 Oe is present stemming from its domain structure. In addition, the uniaxial anisotropy could tailor the resonance frequency from 0.78 and 2.28 GHz for in-plane magnetized FeNi thin film, and 1.3 to 2.4 GHz for FeNi SDs films. Furthermore, a conclusion that a uniaxial anisotropy has no influence on rotatable anisotropy in three magnetic films systems, was yielded.